Virtual Classroom: Need of the Era - Ali, Zeeshan; Agarwal, Parul (International Journal of Psychosocial Rehabilitation, 2020)
Virtual classroom overcomes the challenges and difficulties which present in a traditional classroom. Every student's motive is to concentrate on their studies in the classroom, and this research gives importance and motivation through an e-learning platform that is highly suitable for learning the subjects. The Virtual Classroom is the best well-experienced online teaching strategy. To increase the style of learning new tools and strategies introduced in online classroom environments such as animations and graphics are implemented. The purpose of this article is to offer the concepts on the e-learning platform used to maintain and improve the education and learning system at the universities. In this article, we discuss the various technologies that are being used in the e-learning system. This paper also uses Machine Learning and AI Techniques and virtual classroom explores Machine learning and AI techniques. To create virtual classrooms, distance education relies on the writing and technical support. With the aid of art, map, and live video sessions and many innovations, it is very easy for students to understand the subject matter. The teacher can quickly solve the problems and address them in the smart learning classroom. The implication is that students will more easily gain logical reasoning skills and knowledge in a virtual classroom. Essentially, the Virtual Classroom is better than the traditional classroom.